Bitácora de un viaje. Primeras notas para el estudio del contrato de transporte en Roma y su recepción en la legislación de la nación Argentina = Log of a trip. First notes for the study of the Rome transportation contract and its reception in the legislation of the Argentine nation - Somovilla, Claudia Gabriela (Revista de Derecho Romano, 2023)
El propósito de este estudio inicial consiste en analizar el camino recorrido del contrato de transporte desde Roma y hasta la normativa plasmada en el Código Civil y Comercial de la Nación Argentina. Se informa de manera sintetizada sobre el mismo -dada la riqueza del itinerario-, y con detenimiento en la caracterización del material logrado en determinados momentos considerados relevantes. En cada caso describiendo los resultados de los avances de los trayectos. Y la consideración de aspecto que influyeron positiva o negativamente en la recepción del entendimiento romano por parte del codificador del siglo XXI nacional en particular. ABSTRACT: The purpose of this initial study is to analyze the path traveled by the transport contract from Rome and up to the regulations set forth in the Civil and Commercial Code of the Argentine Nation. It is reported in a synthesized way on it - given the richness of the itinerary - and carefully in the characterization of the material achieved at certain times considered relevant. In each case describing the results of the progress of the routes. And the consideration of aspect that positively or negatively influenced the reception of the Roman understanding by the national 21st century coder in particular.